Ceremony - Silko, Leslie, 1948- (New York : Penguin Books, 1986)
Follows Tayo, a young Native American, after his release from a veteran's hospital following World War II as he searches for meaning and sanity in his life.
Originally published: New York : Viking Press, 1977.
7.4.
Young Adult
Keywords: Indians of North America -- Fiction; World War, 1939-1945 -- Fiction; Historical fiction; Native Americans -- North America -- Fiction; World War, 1939-1945 -- Fiction